A study of anxiety during COVID-19 outbreak among adults in Indonesia - Win Martani, Rahajeng; Mumpuni Yuniarsih, Sri (Proceedings Series on Health & Medical Sciences, 2020)
Coronavirus or well known as COVID 19 emerged in Wuhan (China) in the end of 2019. WHO’s situation report on January 30th 2020 reported 7818 total confirmed cases worldwide, with the majority occurred in China and 82 cases reported in 18 countries outside China. The World Health Organization (WHO) has declared the Covid-19 outbreak a global pandemic as the novel coronavirus continues to rapidly spread worldwide. The rapid increase of COVID-19 new cases makes everyone feel anxious. Anxiety causes a person to respond negatively, therefore people cannot perform good self-management. This study aimed to describe anxiety among people during COVID 19 outbreak in Indonesia. A descriptive study was used to meet the aim of this study. 93 adults and teenagers were recruited and asked to complete a google form questionnaire by self-administrated method. HARS questionnaire was applied as an instrument to measure anxiety. An accidental sampling method was conducted to collect the sample. Data analysis was conducted using descriptive statistic to examine age, living status, educational level, working type, and anxiety level. This study showed that 91.4% respondents were in adult age, 94.6 were living with family member, 66.7% were bachelor and higher, and 36.3% were working as government employees. Anxiety level in this study was divided into three categories. Majority of respondent were having low level of anxiety (88%), 10% were moderate, and the rest (2%) were high anxiety. Highly number of low categories in COVID-19 anxiety means a lot of possibilities. People have an adaptation ability to face every situation in their life. Moreover, this bad situation affect to whole life aspects. Healthcare provider should be prepared as the database of anxiety categories was in low level. Further research should aware wheter this low categories means good or bad for society.